From citizen communication to communication from the conflicts - Macassi Lavander, Sandro (2006)
This arricle deals critically with che norion of media space in relation to the construction of the common good, the representation and access to decision-making. A revision ofinstirurional paradigm is made as well as ofHabermas proposals and of citiz.en communication. Norion of political communiry and debate promotion for creating general interest is quesrioned when there is no equiry no r power equilibrium in acceding media agenda and decision-making. Media space is stated as a scenario of conflicts because of the significance and incidence inpolitical decisions and challenges for redefining media space are analyzed.